Effect of efficient multi-stage indirect evaporative cooling on performance of solar assisted desiccant air conditioning in different climatic zones. - Ahmad, W. (Springer, 2020)
Over the past decade, different variants of desiccant cooling system integrated with direct/indirect evaporative cooler(s) have been simulated and/or analyzed in specific climatic conditions under rather limited operating parameters and for limited durations of time. Complete seasonal and multi-climate performance analyses of solar desiccant cooling system integrated with efficient, indirect Maisotsenko Cycle based evaporative cooler, having combinational installations at process and/or regeneration sides, is rarely investigated and reported. In the current work, multiple configuration variants of solar desiccant cooling system, integrated with multi-stage indirect evaporative cooling technique based on Maisotsenko Cycle, having a designed cooling capacity of 50Â kW are analyzed through a model-based transient simulation approach. Simulations are carried out for a complete typical summer season in northern hemisphere, starting from April to September, using TRNSYS in three different climatic zones including subtropical humid summer (Cfa), hot desert (Bwh) and hot semi-arid (Bsh) conditions. The three selected climatic zones cover around 20 of global world map hosting more than 37 of world population. Each configuration is analyzed in terms of wet bulb and dew point effectiveness using their respective cooling techniques, systemâs thermal coefficient of performance, and solar fraction for each climate zone. It is seen that the configuration using IEC at both process and regeneration sides has the highest values of coefficient of performance and solar fraction in all selected climatic zones compared to others. The respective values of coefficient of performance is 2.28 and solar fraction of 23.84 observed in Bwh while coefficient of performance of 2.03 and solar fraction of 23.33 in Cfa; and coefficient of performance of 2.12 and solar fraction of 46.86 in Bsh climatic zones are noted. The increase of solar fraction in hot and arid climates are expected compared to Cfa. While the value of coefficient of performance for such a system is significantly improved and shows promising prospects to efficiently provide thermal comfort during summer seasons. Â© 2020, Springer-Verlag GmbH Germany, part of Springer Nature.